2019
DOI: 10.18502/ijrm.v17i4.4549
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of amifostine on cyclophosphamide-induced testicular dysfunction in rats: An experimental study

Abstract: Background: Cyclophosphamide (CP) is a well-known alkylating anticancer agent used in the treatment of various malignant and non-malignant tumors. CP may also cause a variety of adverse effects, including reproductive toxicity. Amifostine is known as a cytoprotective drug having antioxidant properties. Objective: To evaluate the possible beneficial effects of amifostine on testicular toxicity induced by CP in rats. Materials and Methods: A total of 35 Sprague-Dawley rats were used in this experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The effect of B. sacra and CP on the weight of the animals, testis weight, and relative weight of testis to body weight were not significantly different. This observation is similar to earlier studies where a single dose of CP did not significantly affect the body weight or weight of the testes significantly 24 .…”
Section: Discussionsupporting
confidence: 92%
“…The effect of B. sacra and CP on the weight of the animals, testis weight, and relative weight of testis to body weight were not significantly different. This observation is similar to earlier studies where a single dose of CP did not significantly affect the body weight or weight of the testes significantly 24 .…”
Section: Discussionsupporting
confidence: 92%
“…CPX-induced changes in urogenital tract in animals are well described in various experimental models of CPX toxicity. The model of single intraperitoneal injection of CPX in a dose of 200 mg/kg is often used with the studied compound administered before or after the CPX injection to induce acute hemorrhagic cystitis or testicular toxicity [10,23,24], but other regimens of CPX administration are also applied, e.g., daily intraperitoneal injection of 100 mg/kg CPX dose for 3 days [25]. We chose 10 days intragastric administration of CPX in a low daily dose of 15 mg/kg with concomitant administration of NaMSA (100 mg/kg) as the potentially protective agent.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that cyclophosphamide caused a down-regulation of the hormones. And it is supported by Kaya et al research, which detailed how cyclophosphamide suppresses the immune system and lowers testosterone levels in the male reproductive system [ 31 ]. Comparing the group treated with 50 mg/kg of Mangifera indica leaf extracts to the group treated with 50 mg/kg of Mangifera indica leaf extracts, a slight counter effect of Mangifera indica leaf extracts was seen.…”
Section: Discussionmentioning
confidence: 99%